How compassionate communities are implemented and evaluated in practice: a scoping review - Dumont, Katia; Marcoux, Isabelle; Warren, Émilie; Alem, Farah; Alvar, Bea; Ballu, Gwenvaël; Bostock, Anitra; Cohen, S. R.; Daneault, Serge; Dubé, Véronique; Houle, Janie; Minyaoui, Asma; et al. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Compassionate communities are rooted in a health promotion approach to palliative care, aiming to support solidarity among community members at the end of life. Hundreds of compassionate communities have been developed internationally in recent years. However, it remains unknown how their implementation on the ground aligns with core strategies of health promotion. The aim of this review is to describe the practical implementation and evaluation of compassionate communities. Methods We undertook a scoping review of the empirical peer-reviewed literature on compassionate communities. Bibliographic searches in five databases were developed with information specialists. We included studies in English describing health promotion activities applied to end-of-life and palliative care. Qualitative analysis used inductive and deductive strategies based on existing frameworks for categorization of health promotion activities, barriers and facilitators for implementation and evaluation measures. A participatory research approach with community partners was used to design the review and interpret its findings. Results Sixty-three articles were included for analysis. 74.6% were published after 2011. Health services organizations and providers are most often engaged as compassionate community leaders, with community members mainly engaged as target users. Adaptation to local culture and social context is the most frequently reported barrier for implementation, with support and external factors mostly reported as facilitators. Early stages of compassionate community development are rarely reported in the literature (stakeholder mobilization, needs assessment, priority-setting). Health promotion strategies tend to focus on the development of personal skills, mainly through the use of education and awareness programs. Few activities focused on strengthening community action and building healthy public policies. Evaluation was reported in 30% of articles, 88% of evaluation being analyzed at the individual level, as opposed to community processes and outcomes. Conclusions The empirical literature on compassionate communities demonstrates a wide variety of health promotion practices. Much international experience has been developed in education and awareness programs on death and dying. Health promotion strategies based on community strengthening and policies need to be consolidated. Future research should pay attention to community-led initiatives and evaluations that may not be currently reported in the peer-review literature.